PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN CONTEXTUAL TEACHING AND LEARNING PADA MATERI MATRIKS UNTUK KELAS XI SMA - Fadlina Ruhama (Departemen Matematika, 2021)
The 2013 curriculum is designed so that students can be active, creative and innovative and enthusiastic in constructing their own knowledge. However, in reality, students tend to be passive in learning and are not used to constructing their own knowledge. The teaching materials used are Kemendikbud 2013 books and LKPD which are designed for other people. Due to time and IT constraints, LKPD has not been designed specifically. This resulted in the absence of a valid and practical LKPD. This study aims to produce LKPD based on the Contextual Teaching and Learning (CTL) approach that is valid and practical, for class XI high school students. This type of research is design research that uses the Plomp development model, which consists of the preliminary research stage and the prototype stage. The preliminary research stage consists of curriculum analysis, concept analysis and student analysis. The prototyping stage consists of 4 stages carried out in the LKPD design. In prototype 1, a self-evaluation (self-evaluation) was carried out. In prototype 2, an expert review was carried out which was evaluated by experts to obtain a valid prototype. In prototype 3, a one-to-one evaluation was carried out by testing the LKPD on three students with heterogeneous abilities level. In prototype 4, a small group evaluation stage was carried out for six students with heterogeneous ability levels, which aimed to determine the practicality of the LKPD. From the research that has been done, it is found that the CTL Approach-Based Student Worksheet on the subject matrix has a validity level of 88.98% with very valid criteria (based on three experts, namely two mathematicians and one linguist). LKPD also has a level of practicality with a very practical category of 85.76% by students and 89.94% by educators.Keywords - LKPD, Contextual Teaching and Learning, valid, practica